The Oxford companion to the English language (Oxford Univ, 1992)
This book covers virtually every aspect of the English language as well language in general. The range of topics is remarkable, offering a goldmine of information on writing and speech (including entries on grammar, literacy terms, linguistics, rhetoric, and style) as well as on such wider issues as sexist language, bilingual education, child language acquisition, and the history of English. This book also provides bibliographies for the larger entries, generous cross-referencing, etymologies for headwords, a chronology of English from Roman times to 1990, and index of people who appear in entries or bibliographies